Effective mortality thresholds for reporting suspicion of highly pathogenic avian influenza in mule ducks - Sébastien Lambert; Caroline Godard; Timothée Vergne (Veterinary Research)
Abstract Effective mortality thresholds are critical for timely reporting and management of highly pathogenic avian influenza. Using standard modelling techniques, we evaluated the performance of different mortality thresholds in mule duck flocks. Using an eightfold increase of the mortality for two consecutive days compared to the average mortality the previous week led to a perfect classification of all flocks used for validation (12 affected and 18 non-affected flocks). A fixed daily threshold of 0.25% showed a perfect sensitivity and a good specificity (3 false positives/18). Our results fill a knowledge gap and can inform HPAI surveillance policy in non-vaccinated mule ducks.